Islamic junior high school students - Rifiyani, Andri Jamaul; Mustofa, Mutmainnah; Ubaidillah, M. Faruq; Lee, Huan Yik; Putra, Suatmo Pantja (Journal on English as a Foreign Language, 2023)
The L2 motivational self-system (L2MSS) has been extensively investigated in multiple contexts. However, few studies have explored its correlation with Islamic junior high English students